2021
DOI: 10.1039/d0fo02623a
|View full text |Cite
|
Sign up to set email alerts
|

Plant sterol ester of α-linolenic acid ameliorates high-fat diet-induced nonalcoholic fatty liver disease in mice: association with regulating mitochondrial dysfunction and oxidative stress via activating AMPK signaling

Abstract: Plant sterol ester of α-linolenic acid prevents nonalcoholic fatty liver disease by improving mitochondrial function, modifying lipid metabolism, and inhibiting oxidative stress via AMPK signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 65 publications
3
9
0
Order By: Relevance
“…Moreover that, mitochondrial dysfunction manifested by mitochondrial swelling and loss of cristae. Similar to our findings, these structural and ultrastructural changes of hepatocytes have been observed in animal models and patients of NAFLD [16], [17].…”
Section: : Photomicrographs Of Immunostained Liver Sections For Caspa...supporting
confidence: 92%
“…Moreover that, mitochondrial dysfunction manifested by mitochondrial swelling and loss of cristae. Similar to our findings, these structural and ultrastructural changes of hepatocytes have been observed in animal models and patients of NAFLD [16], [17].…”
Section: : Photomicrographs Of Immunostained Liver Sections For Caspa...supporting
confidence: 92%
“…A potential clue for the role of ROS in NAFLD progression arises from the therapeutic use of antioxidants. Antioxidants such as sterol ester of alpha‐linolenic acid, 211 physalin B, 212 N‐acetyl cysteine, 213 or vitamin E and vitamin C 214 showed beneficial effects against liver injury, including fibrosis, in the context of NAFLD. Still, a meta‐analysis of randomized trials for treating NAFLD found that those including antioxidants gave mixed results 215 .…”
Section: Ros and Rns Culprits Or Bystanders Of Nafld Progressionmentioning
confidence: 99%
“…This signaling pathway serves an important role in mitochondrial biogenesis ( 26 ). The PGC-1α/NRF1/TFAM signaling pathway has previously been demonstrated to be involved in mitochondrial biogenesis in numerous diseases ( 27 , 28 ). Jiang et al ( 29 ) demonstrated that perampanel could improve mitochondrial biogenesis in neuronal cells via activation of the PGC-1α/NRF1 signaling pathway, which thereby exerts an anti-epileptic effect.…”
Section: Discussionmentioning
confidence: 99%